Intraday variability of AGNs in the southern hemisphere - Cimo, G.; Ellingsen, S.; Senkbeil, C.; McCulloch, P.; Bignall, Hayley; Kedziora-Chudczer, L. (http://pos.sissa.it/, 2006)
Understanding of the spectral and polarimetric characteristics of rapidly scintillating blazars is fundamental in order to describe both the innermost (sub-pc) regions of these compact objects and the interstellar medium responsible for the scintillation. A multi frequency analysis of the intraday variability in PMN J1326-5256, based on the combination of Australia Telescope Compact Array observations with the data from the monitoring projects at the University of Tasmania, will be described. Some implications concerning the structure of compact radio cores and the properties of the interstellar medium will be discussed.